Construction and efficacy evaluation of an early warning scoring system for septic shock in patients with digestive tract perforation: A retrospective cohort study - Chen, Peiling; Gao, Jingqi; Li, Jun; Yu, Rongguo; Wang, Ling; Xue, Fangqin; Zheng, Xiaochun; Gao, Ling; Shang, Xiuling (Frontiers in Medicine, 2022)
Objective: To establish an early warning scoring system for septic shock in patients with digestive tract perforation (DTP) and evaluate its diagnostic efficacy. Methods: Patients with surgically confirmed or clinically diagnosed DTP admitted to the Department of Intensive Care Medicine of Fujian Provincial Hospital from June 2012 to October 2021 were retrospectively analyzed. General demographic characteristics, perforation-related information, vital signs, common laboratory indicators, and common ICU scores (Glasgow Coma Scale score, Acute Physiology and Chronic Health Evaluation-Ⅱ score，Sequential Organ Failure Assessment score ) were collected. The patients were divided into shock group and non-shock group according to whether the patients had septic shock during hospitalization. The risk factors of septic shock were screened by basic statistical analysis and multivariate Logistic regression analysis. The receiver operating characteristic curve was drawn to determine the cut-off value of the continuous indicators and discretized with reference to clinic, and the corresponding score was set according to the β regression coefficient of each variable. Results: A total of 176 patients with DTP were included. The average age of the patients was 64.13±14.67 years old, and 74.40% were males. The incidence of septic shock was 30.11% (53/176). Multivariate Logistic regression analysis showed that the highest heart rate≥105 beats/min, Glasgow Coma Scale score≤14 points, lactic acid≥5.75mmol/L, procalcitonin≥41.47ug/L, C-reactive protein≥222.5mg/L were independent risk factors for septic shock in patients with DTP. The total score of clinical diagnostic scoring system of septic shock in patients with DTP was 6 points, including the highest heart rate≥105 beats/min (1 point), lactic acid≥5.75mmol/L (2 points), procalcitonin≥41.47ug/L (1 point), C-reactive protein≥222.5mg/L (1 point), and Glasgow Coma Scale score ≤14 points (1 point). The area under ROC curve (AUC) of this scoring system was 0.789 and the 95% confidence interval was 0.717-0.860 (P<0.001); when the optimal cut-off value was 2.5, the sensitivity and specificity were 54.70% and 87.80%, respectively. Conclusion: This new score system has its certain clinical value and has important guiding significance for clinicians to judge the prognosis of patients with DTP in time.